"Zwykły człowiek" jako konstrukt myślowy – z obserwacji prasy tabloidowej - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The purpose of the article is to answer the question, if editors of the tabloid newspapers see their readers and how this vision discloses in a press. The authoress thinks that the journalists expectation have not much in common with a practical of the editorial office. These difference are visible in a editorial level and as in a function of the press. It is often used a phrase “ a common man” for the tabloid readers. It says, that he is poor educationed, have a low taste, easy care of the emotions and can understand only short, unambiguous remittances. Journalism materials with are put in the polish tabloids (“ Fakt” , “Super Express”) show that their precision requires complex skills. Surmise, tabloid readers instead of the enjoyment and diminished information get a product, which is first of all to serve to manipulate their image of reality and has a influence for their suspection.